Degradation of antibiotics in aquaculture wastewater by bio-nanoparticles: A critical review - Mohd Noor, Nur Nabilah; Kamaruzaman, Nur Hazirah; Adel Al-Gheethi, Adel Al-Gheethi; Radin Mohamed, Radin Maya Saphira; Md. Sohrab Hossain, Md. Sohrab Hossain (ASEJ, 2022)
The environmental pollution caused by antibiotics has seriously affected human health and the ecosystem. Antibiotics have been known as pollutants due to their persistence and adverse impact on aquatic ecosystem. However, critical reviews for antibiotics in the wastewater and the most recent technologies used to eliminate antibiotics are very rare. The current review summarized the removal strategies for various antibiotics using photocatalysis of bio-nanoparticles and these emphases the novelty in the present work. The comparison between different methods and factors affecting the photocatalysis process was discussed. Based on the review process of the studies in the literature review it was appeared that zinc nanoparticles are among the semiconductors with a good electrical, mechanical, and optical semiconductor oxide which exhibited high efficiency in the photocatalysis process. The biosynthesized nanoparticles have high applicability in the photocatalysis of antibiotics because of of absence the toxic by-products and secondary compounds, which might have a negative effect on the environment. However, the fate of degraded antibiotics in the environment still needs more studies to confirm the absence of their activity in inducing the microbial resistance.